Silencing of long non-coding RNA CCAT2 depressed malignancy of oral squamous cell carcinoma via Wnt/β-catenin pathway - Yuji Ma; Xuanhao Hu; Chao Shang; Ming Zhong; Yan Guo (Tumor Biology)
Oral squamous cell carcinoma is a common and lethal malignancy affecting the head and neck region. CCAT2 (colon cancer–associated transcript 2) gene is affiliated with long non-coding RNAs, which are often found to have important regulatory roles in cancers. This study aims to assess the expression and clinical significance of CCAT2 gene, identify its malignant biological behaviors, and explore the possible mechanisms in oral squamous cell carcinoma. CCAT2 expression was detected by quantitative real-time polymerase chain reaction, and its relationship with clinical factors was assayed using the Kaplan–Meier survival curve. The biological behaviors of CCAT2 and its potential mechanisms in oral squamous cell carcinoma were explored by the combined use of CCAT2 knockdown technology and the Wnt/β-catenin pathway agonist lithium chloride (LiCl). Our results showed that CCAT2 functioning as a potential oncogene was upregulated in oral squamous cell carcinoma. CCAT2 with high expression level was correlated with poor differentiation, higher T stage, and clinical stage, which made CCAT2 to be a prognostic biomarker in oral squamous cell carcinoma. LiCl-activated Wnt/β-catenin signaling pathway could partly restore the CCAT2-mediated malignant biological behaviors of oral squamous cell carcinoma cells by suppressing β-catenin, CCND1, and MYC and activating glycogen synthase kinase 3 beta expression. These findings might assist in the discovery of novel potential diagnostic and therapeutic target for oral squamous cell carcinoma, thereby improve the effects of clinical treatment in patients.